Revitalising the Role of Foster Parents in Supporting Santri Achievement at Nurul Jadid Islamic Boarding School - Ahmad Zubaidi; Ainil Yaqinah (At-Tarbiyat, 2023)
Boarding school is an institution that has an important role in producing a superior young generation. The purpose of this study hopes to provide information and input to the parties concerned in improving the achievement of students in Islamic Boarding School, especially the role of foster guardians. Foster guardians are foster parents in Islamic Boarding School who are responsible for life and education in Islamic Boarding School. Foster guardians play a very important role in supporting student achievement, both in the academic and non-academic fields. However, in practice, the role of each foster guardian is less than optimal. This is caused by several factors, including the low understanding of foster guardians about their roles and responsibilities, as well as the lack of communication and coordination between foster guardians and the boarding school. This research uses a qualitative descriptive method using several stages of situation analysis, conducting interviews, reducing data, making discussions and drawing conclusions. The results of this study indicate that the involvement of foster guardians in supporting students' achievements is quite high, in this case the foster guardians have several roles in the Islamic Boarding School to assist students, including: assisting students in the spiritual, emotional, and academic fields of students.